Efficacy and Safety of Biphenyl Dimethyl Dicarboxylate and Ursodeoxycholic Acid Combination in Chronic Hepatitis Related to Metabolic Syndrome Components - Nae-Yun Heo (The Korean Journal of Gastroenterology, 2021)
Backgrounds/Aims: Steatohepatitis related to metabolic syndrome is a chronic liver disease prevalent in patients not only with non-alcoholic steatohepatitis but also with alcoholic liver disease and chronic viral hepatitis. On the other hand, there is limited data on the effects of hepatotonic agents in these patients. Therefore, this study evaluated the efficacy of a combined hepatotonic agent in this population. Methods: Thirty-three adults with chronic hepatitis and one or more components of metabolic syndrome were assigned randomly to receive biphenyl dimethyl dicarboxylate/ursodeoxycholic acid or a placebo for 24 weeks. The primary outcome was the normalization of ALT (≤40 U/L). The secondary outcomes were the change in controlled attenuation parameter, transient elastography, and Chronic Liver Disease Questionnaire score. Results: The 33 patients were assigned randomly to two groups. Eight (50%) of 16 patients who received the intervention drug showed the normalization of ALT, whereas only one (6%) of 17 patients in the placebo group did so. In contrast, the change in controlled attenuation, transient elastography, and Chronic Liver Disease Questionnaire were similar in the two groups. ALT was changed significantly during the four assessment periods, and this change was affected by the group. The interaction between the group and time was also significant. AST was changed significantly during the same period. This change was not affected by the group. Conclusions: Biphenyl dimethyl dicarboxylate/ursodeoxycholic acid combination reduced ALT in chronic liver disease related to metabolic syndrome. On the other hand, there is no evidence that this leads to improved hepatic steatosis and fibrosis within 6 months.